Biochemistry Mycobacterium Tuberculosis Treated with Anti-Isoniazid Treatment (Jaringan Laboratorium Medis, 2023)
Mycobacterium tuberculosis exposed to Isoniazid experienced drug resistance due to morphological and selection factors, with Isoniazid concentrations of 0.5 μg / ml with a contact time of 24 hours, 48 hours, 72 hours, 96 hours, the results obtained in testing for NaCl 5% Kruskal wallis obtained sig 0.005 results there is a treatment effect on growth While in the semi-quantitative catalase test, a sig value of 0.007 was obtained with p